Encyclopedia of Contemporary German Culture. - Sandford, John (Taylor and Francis, 2013)
With more than 1,100 entries written by an international group of over 150 contributors, the Encyclopedia of Contemporary German Culture brings together myriad strands of social, political and cultural life in the post-1945 German-speaking world. With a unique structure and format, an inclusive treatment of the concept of culture, and coverage of East, West and post-unification Germany, as well as Austria and Switzerland, the Encyclopedia of Contemporary German Culture is the first reference work of its kind. Containing longer overviews of up to 2,000 words, a.